A preventive maintenance model with a two-level inspection policy based on a three-stage failure process - Wang, Wenbin; Zhao, Fei; Peng, Rui (Reliability engineering & system safety, 2014)
Inspection is always an important preventive maintenance (PM) activity and can have different depths and cover all or part of plant systems. This paper introduces a two-level inspection policy model for a single component plant system based on a three-stage failure process. Such a failure process divides the system′s life into three stages: good, minor defective and severe defective stages. The first level of inspection, the minor inspection, can only identify the minor defective stage with a certain probability, but can always reveal the severe defective stage. The major inspection can however identify both defective stages perfectly. Once the system is found to be in the minor defective stage, a shortened inspection interval is adopted. If however the system is found to be in the severe defective stage, we may delay the maintenance action if the time to the next planned PM window is less than a threshold level, but otherwise, replace immediately. This corresponds to the well adopted maintenance policy in practice such as periodic inspections with planned PMs. A numerical example is presented to demonstrate the proposed model by comparing with other models. •The system′s deterioration goes through a three-stage process, namely, normal, minor defective and severe defective.•Two levels of inspections are proposed, e.g., minor and major inspections.•Once the minor defective stage is found, instead of taking a maintenance action, a shortened inspection interval is recommended.•When the severe defective stage is found, we delay the maintenance according to the threshold to the next PM.•The decision variables are the inspection intervals and the threshold to PM.